2021
DOI: 10.31219/osf.io/g2kza
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G6PD deficiency is a common genetic trait that can protect heterozygotes from dying from malaria

Abstract: G6PD deficiency is a common genetic trait that can protect heterozygotes from dying from malaria (save in the extremely tiny fraction of individuals who have CNSHA). AHA in a G6PD-deficient child or adult, on the other hand, is a medical emergency that, if not treated promptly and properly, can be fatal. Fava bean consumption is the most common cause of AHA: favism is seen in at least 35 countries, with thousands of cases reported each year. Both primaquine and rasburicase have been linked to iatrogenic deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Progranulin's specific actions are unknown; nevertheless, it is thought that this protein may have neurotrophic and synaptic effects on the central nervous system. In addition, people with GRN mutations have been discovered to have autoimmune diseases (74). Progranulin was shown to be involved in the control of inflammation in mouse models through antagonistic effects of tumor necrosis factor- (75).…”
Section: The Grn Mutation Is Being Targetedmentioning
confidence: 99%
“…Progranulin's specific actions are unknown; nevertheless, it is thought that this protein may have neurotrophic and synaptic effects on the central nervous system. In addition, people with GRN mutations have been discovered to have autoimmune diseases (74). Progranulin was shown to be involved in the control of inflammation in mouse models through antagonistic effects of tumor necrosis factor- (75).…”
Section: The Grn Mutation Is Being Targetedmentioning
confidence: 99%
“…The inconsistency of the sRAGE level owing to cigarette smoking was discussed by Prasad et al (80). Smoking, on the other hand, causes a quick and substantial drop in serum sRAGE, according to research (81). Furthermore, smoking has been shown to have an immediate and transient influence on serum sRAGE (81).…”
Section: In Copd the Age-rage Axis And Srage Play A Rolementioning
confidence: 99%
“…Smoking, on the other hand, causes a quick and substantial drop in serum sRAGE, according to research (81). Furthermore, smoking has been shown to have an immediate and transient influence on serum sRAGE (81). Because the results of these studies are inconsistent, various authors have reported and suggested that more research is needed before sRAGE can be considered a potential biomarker for COPD (82).…”
Section: In Copd the Age-rage Axis And Srage Play A Rolementioning
confidence: 99%
“…A large, cohort research comprising 132 participants with CKD discovered that urine ET-1 levels increased in individuals with SLE, even when their GFR was normal (72). Giant mesangial cell proliferation and matrix generation is associated with the presence of ET-1 in SLE patients (73,74). Renal ET-1 and ETB receptors are present in NZB/WF1 mice (34).…”
Section: Glomerulonephritis Renal Lupusmentioning
confidence: 99%